If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -15 = 8x + 7 Reorder the terms: -15 + 3x = 8x + 7 Reorder the terms: -15 + 3x = 7 + 8x Solving -15 + 3x = 7 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -15 + 3x + -8x = 7 + 8x + -8x Combine like terms: 3x + -8x = -5x -15 + -5x = 7 + 8x + -8x Combine like terms: 8x + -8x = 0 -15 + -5x = 7 + 0 -15 + -5x = 7 Add '15' to each side of the equation. -15 + 15 + -5x = 7 + 15 Combine like terms: -15 + 15 = 0 0 + -5x = 7 + 15 -5x = 7 + 15 Combine like terms: 7 + 15 = 22 -5x = 22 Divide each side by '-5'. x = -4.4 Simplifying x = -4.4
| 16=.25h | | -9-8(1.4H)=-17 | | -2y=3y+5 | | -12=3x+9-6x | | 25-3x=1 | | 2(l+0.4l)=364 | | 56-(3c+4)=4(c+7)+3 | | 0.07y+0.02x=5 | | 9x-12+85=0 | | -3/4r-1 | | U^2-3v=0 | | -z/2 | | (2x+8)+(3x+16)+(4x-18)+(3x-7)+(2x+25)=720 | | 8+4v=-4 | | 4a+6-3a-2= | | S/-3=2 | | h=2*3.14*r^2+2*3.14*r*16.2 | | 25n-40=-62 | | 3/4(8y-12)= | | .75t=50 | | F(x)=12x-6 | | 8(-5+4)= | | .75t=.50 | | (2y+9)(2y+9)=81 | | (4-2j)/(2-1j) | | 5.26s-2.01=-8.94 | | -2g+7= | | -9s+18-18=18s-4-2 | | 7v+224=-84v | | 3v+9+v=2v-2+3 | | -38-37= | | 10+5x-x=10+4x+4 |